Leah Connelly leaving Raton - Woodworth, Lil (Raton Range Raton, New Mexico, 1976)
Newspaper Article on Leah Connelly and a little history on her life. She is moving to a retirement home in Carlsbad, New Mexico.
Master list item #: 64
File location is in the Raton File Cabinet
Keywords: Connelly. Leah; Bergen, William; Bergen, (Mrs); Connelly, Gus; Connelly, Bill; Connelly, Jack; Connelly, Darlene; Stockton, Margoree; Mackie, Barbara; Landsun Retirement home; Raton High School; Moreno Valley School; Rocky Mountain and Pacific School Board; Blossburg Mercantile Company; Daisy Dairy; Raton Country Club; Methodist Church; New Mexico Boys School; Local History; Biography; Life and Customs; Retirement; Teaching; Community; Birthday party; Raton, New Mexico; Carlsbad, New Mexico; Shellsburg, Iowa; Moreno Valley, New Mexico; Van Houten, New Mexico; Springer, New Mexico